The Mind Map Learning Model Increase The Motivation and Learning Outcomes of Sixth Graders at SD Negeri 2 Klunggen - Aprianto, Eko (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The learning outcomes of grade VI students at SD Negeri 2 Klunggen are still low, with an average score of 55.24. The formulation of the problem in this study is how the learning process with the Mind Map method can improve the learning outcomes of class VI SDN 2 Klunggen students. The purpose of this study is the Mind Map learning process to improve motivation and learning outcomes of class VI students. his research was conducted on the sixth grade students with a total of 22 students. Research planning is carried out collaboratively with colleagues. The results of the research that occurred during the action research was an increase in the average learning from 55.24 in the initial conditions to 66.67 in the first cycle and 83.33 in the second cycle. In addition, the results of the study are also related to the increase in student learning mastery from 23.81% in the initial conditions to 66.67% in the first cycle and 95.24% in the second cycle. It is concluded that the action through the use of the Mind Map learning model can improve student learning outcomes.